CÓDIGO ORGÁNICO INTEGRAL PENAL, EN CONTRADICCIÓN CON LA CONSTITUCIÓN Y LOS TRATADOS INTERNACIONALES - Romero Rodríguez, Marco Vinicio (2016)
Ecuador has a history of important social struggle since the colonial era, to free from Spanish rule, until today to achieve social and national break release, in this context, today we see problems persist in the area legal, because to know the laws always were imposed for the benefit of a few, which are those that have been succeeding in power, in the I course transcurso time have always persisted facts of prosecution, persecution, vilification and incarceration of social leaders and political leaders defend public causes, configuring a kind of criminalization of social struggle, due to the ambiguity of our legislation on criminal offenses that were imposed by dictatorial governments in the past and which are kept in the Code of Criminal Integral. This penal legislation inconsistent, is not appropriate to state protection afforded by the Constitution of Montecristi, therefore, criminal legislation, is used and enforced by state power through the judicial function that has given up their autonomy to government service shift grossly intervening in the ordinary courts to impose terms as to judge the legitimacy of the acts of defending the people, jailing and silencing freedom of social protest that is protected by the Constitution of the Republic as the right to resistance. Under this insight, we can say that in Ecuador whose fundamental principle ranks it as State Constitutional Rights and Justice, human rights are violated, what distance the state of compliance with international treaties and agreements, as the effective remedy rights and guarantees, as well as justice, have become a mere statement on paper. The method that allowed this research was to develop the scientific method, which determined the objective reality of the legal issues on the criminalization of social protest. As methods and techniques of observation, analysis and synthesis is used, as well as auxiliary techniques bibliographic or documentary signing; and, as a technique for gathering empirical data survey and interview.